2014
DOI: 10.14429/djlit.34.6586
|View full text |Cite
|
Sign up to set email alerts
|

Use of Information and Communication Technology by Visually-impaired Students: A Study in University of Calicut, Kerala

Abstract: The purpose of this study was to investigate the use of Information and communication technology (ICT) by the visually impaired students in Calicut University, Kerala. Semi-structured interviews were employed to collect data from a representative sample of 100 visually impaired students from the departments and affiliated colleges of the University. The study found that a large majority of the students are computer literates and use mobile phones frequently. A good number of them use screen readers in their mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Several studies have investigated the basic ICT skills and ICT usage of individuals with VI (Haneefa & Syamili, 2014 ; Şimşek et al, 2010 ; Soman & Sudhier, 2015 ; Yılmaz, 2019 ), their technological needs (Fuglerud, 2011 ), as well as the challenges they face related to technology access (Thongma-eng, 2015 ), and the related importance of these technologies (Ashraf et al, 2017 ; Douglas, 2001 ; Kumar & Sanaman, 2013 ; Okonji et al, 2020 ). These studies have revealed that individuals with VI can perform basic computer skills such as preparing documents, searching for information using the Internet, as well as sending emails and communicating with friends.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the basic ICT skills and ICT usage of individuals with VI (Haneefa & Syamili, 2014 ; Şimşek et al, 2010 ; Soman & Sudhier, 2015 ; Yılmaz, 2019 ), their technological needs (Fuglerud, 2011 ), as well as the challenges they face related to technology access (Thongma-eng, 2015 ), and the related importance of these technologies (Ashraf et al, 2017 ; Douglas, 2001 ; Kumar & Sanaman, 2013 ; Okonji et al, 2020 ). These studies have revealed that individuals with VI can perform basic computer skills such as preparing documents, searching for information using the Internet, as well as sending emails and communicating with friends.…”
Section: Introductionmentioning
confidence: 99%
“…successfully master their age-appropriate curriculum. In the field of computer science, traditional physical textbooks are replaced by digital textbooks (Haneefa and Syamili, 2014;Bhardwaj and Kumar, 2017;Eligi and Mwantimwa, 2017;Leo et al, 2017). The educational resources can be accessed on a computer or a comparable electronic device.…”
Section: Journal Of Disability Research 2024mentioning
confidence: 99%
“…Research efforts to provide non-visual GUI accessibility have shifted to web-based interfaces as web-application development became more prevalent. (Takagi, Saito, Fukuda, & Asakawa, 2007;Lazar et al, 2007;K. & C., 2014).…”
Section: Related Workmentioning
confidence: 99%